A MENGOPTIMALKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN BERPIKIR KRITIS MELALUI PEMBELAJARAN CORE DAN I-CARE DENGAN APLIKASI GEOMETRYX DI SEKOLAH MENENGAH PERTAMA DI LEBAK, BANTEN : Berpikir Kritis, Inti, Geometryx, ICARE, Kemampuan Pemecahan Masalah Matematis. - Yulianto, Dwi; Moh Rizal Umami; Syahrul Anwar (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
The background of this research arises from the need to improve the quality of mathematics learning at the junior high school level, especially regarding mathematical problem-solving skills and critical thinking. With the challenges of globalization and technological advances, the use of the Geometryx application as a support for Core and I-CARE learning is considered an innovative step in providing better understanding to students. This study aims to investigate the influence of Core and I-CARE learning supported by the Geometryx application on the mathematical problem-solving and critical thinking skills of junior high school students in Lebak Regency, Banten. The research method used is Quasi-Experiment with a 2×3 factorial design, involving 1,948 students from 10 State Junior High Schools in Lebak, Banten. The sample was selected using cluster random sampling technique, with the seventh-grade classes of SMPN 2 Sajira and SMPN 1 Cibeber as samples, each consisting of Core and ICARE classes with 104 students through cluster random sampling. Data were collected through a pretest from two essay questions of space and shape content AKM, and posttests of mathematical problem-solving ability (2 essay questions) and critical thinking ability (2 questions). Data analysis used two-way ANOVA (Two-way ANOVA). The results showed that 1) there is an influence between Core and I-CARE learning models assisted by the Geometryx application on students' problem-solving abilities in the high category, 2) there is an influence between Core and I-CARE learning models assisted by the Geometryx application on students' mathematical critical thinking abilities in the high category, and 3) there is an influence of Core and I-CARE learning models assisted by the Geometryx application on students' problem-solving and critical thinking abilities in the high category. The results of this study have significant implications for the world of mathematics education in SMPN Lebak Regency, Banten. The use of Core and I-CARE learning models, supported by the Geometryx application, contributes positively to the mathematical problem-solving and critical thinking skills of students.